Unequal Freedom: How Race and Gender Shaped American Citizenship and Labor - Masur, Kate (Labour / Le Travail, 2004)
The article reviews the book, "Unequal Freedom: How Race and Gender Shaped American Citizenship and Labor," by Evelyn Nakano Glenn.